The Influence of Brand Trust and Satisfaction towards Consumer Loyalty of a Local Cosmetic Products Brand X among Generation Z - Moh. Djemdjem Djamaludin; Annisa Fahira (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2023)
The increasing demand for cosmetic products during the Covid-19 pandemic has encouraged companies to increase consumer trust and satisfaction so that consumers remain loyal to one brand, including a well-known local cosmetic product brand. This study aims to analyze the influence of brand trust and satisfaction towards consumer loyalty of a local cosmetic products brand X among generation Z. This study used a cross-sectional study design. Three hundred and eighteen respondents were collected by voluntary sampling. Data were collected through Google Forms online questionnaire and processed Structural Equation Modeling. The results showed that gender, age, education, and monthly income were positively and significantly related to brand trust. Age, monthly income, frequency of purchasing local cosmetic brand X, types of local cosmetic brand X products purchased, and duration of use of local cosmetic brand X products have a positive and significant relationship with consumer loyalty. The results of the SEM show that brand trust positively and significantly influences consumer satisfaction and loyalty. In addition, consumer satisfaction positively and significantly influences consumer loyalty. The lack of consumer confidence in the materials used by brand X in production indicates that consumer literacy regarding products still needs to improve.